pH-responsive, core-shell magnetite-silver nanoparticles for the guided transport and delivery of nucleotide cargoes : an avenue for highly-targeted gene therapies (2019)
Over the past few years, gene therapies have attracted much attention for the development of therapies for various conditions including cancer, neurodegenerative diseases, protein deficiencies, and autoimmune disorders. Despite the benefits of this approach, several challenges are yet to be solved to reach clinical implementation eventually. Some of these challenges include low transfection rates, limited stability under physiological conditions, and low specificity towards the target cells. An avenue to overcome such issues is to deliver the therapies with the aid of potent cell-penetrating vectors, which include viral and non-viral vehicles. Non-viral vectors, such as nanostructured materials, have been successfully tested in drug and gene delivery. Here we propose the development of a nanostructured core-shell cell-penetrating vehicle composed of magnetite at the core, surrounded by a silver shell. A subsequent superficial conjugation of a pH-responsive polymer was used to assure that the vehicle can carry and release circular DNA. The obtained nanoconjugates were characterized by UV-Vis spectrophotometry, dynamic light scattering (DLS), thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR), and scanning electron microscope equipped with energy dispersive spectroscopy (SEM+EDS). Finally, a DNA load and delivery test were conducted to calculate the efficiency of the vehicle. The proposed nanoconjugate was capable of loading around 16% of the added DNA and released in a delivery stage. The study presented here provides a route for the development of gene delivery systems based on core-shell magnetic nanoparticles and pH-responsive polymers. Also, it highlights a methodology for the synthesis, functionalization, and loading of a circular DNA vector with the size typical of those for applications in CRISPR/Cas9 editing systems.